Clinical Characteristics of COVID-19 in Patients: A Meta-Analysis (Indian Journal of Forensic Medicine & Toxicology, 2021)
An outbreak of coronavirus disease 2019 (COVID-19) was detected in Wuhan, China in December 2019, the causative agent is severe acute respiratory coronavirus 2 (SARS-Co-2). The virus spread quickly to other areas and countries and the disease has become pandemic. This meta-analysis study was carried out to evaluate the clinical characteristics and to assess the prevalence of comorbidities in COVID-19 confirmed patients from January 1, 2020 to December 1, 2020. Totally, 5580 cases were involved in this study, (55.2%) of them were males, the predominant clinical symptoms of COVID-19 patients were fever, cough, and fatigue (61.9, 50.1%, and 34.1% respectively). The most frequent comorbidities were hypertension, diabetes, as well as cardiovascular and cerebrovascular diseases (13.1%, 7.4 %, and 5.9% respectively). The majority of the patients in this study were male, the most prevalent signs and symptoms were fever, cough, and fatigue. The highly repeated comorbidities in the cases were hypertension, diabetes, also cardiovascular and cerebrovascular diseases.
Keywords: COVID-19, clinical characteristics, comorbidity, meta-analysis